Extent of radiological response does not reflect survival in primary central nervous system lymphoma. Issue 1 (15th February 2021) - van der Meulen, Matthijs; Postma, Alida A; Smits, Marion; Bakunina, Katerina; Minnema, Monique C; Seute, Tatjana; Cull, Gavin; Enting, Roelien H; van der Poel, Marjolein; Stevens, Wendy B C; Brandsma, Dieta; Beeker, Aart; et al.
Abstract: Background: In primary central nervous system lymphoma (PCNSL), small enhancing lesions can persist after treatment. It is unknown whether a difference in response category (complete response [CR], complete response unconfirmed [CRu], or partial response [PR]) reflects survival. We aimed to determine the value of a central radiology review on response assessment and whether the extent of response influenced progression-free and/or overall survival. Methods: All patients in the HOVON 105/ALLG NHL 24 study with at least a baseline MRI and one MRI made for response evaluation available for central review were included. Tumor measurements were done by 2 independent central reviewers, disagreements were adjudicated by a third reviewer. Crude agreement and interobserver agreement (Cohen's kappa) were calculated. Differences in progression-free and overall survival between different categories of response at the end-of-protocol-treatment were assessed by the log-rank test in a landmark survival-analysis. Results: Agreement between the central reviewers was 61.7% and between local and central response assessment was 63.0%. Cohen's kappa's, which corrects for expected agreement, were 0.44 and 0.46 (moderate), respectively. Progression agreement or not was 93.3% (kappa 0.87) between local and central response assessment. There were no significant differences in progression-free and overall survival between patients with CR, CRu, or PR at the end-of-protocol-treatment, according to both local and central response assessment. Conclusions: Reliability of response assessment (CR/CRu/PR) is moderate even by central radiology review and these response categories do not reliably predict survival. Therefore, primary outcome in PCNSL studies should be survival rather than CR or CR/CRu-rate.